MEMPERSIAPKAN PUSTAKAWAN KREATIF UNTUK MELAYANI PEMUSTAKA ANAK - Sagita, Gita; Jayanti Fakhlina, Resty (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2023)
This research aims to find out what creative efforts librarians can make to provide excellent service to children's readers. The author uses a qualitative method with a literature review approach using the Publish or Perish, Prisma2000, and VOSviewer applications to collect supporting theories for ideas that can be used by librarians serving children's libraries. Libraries should be able to provide benefits to users of all age categories, including children. The character possessed by child users is believed to be quite unique and a challenge in itself, therefore librarians can provide innovation in routine service activities, as well as adopt other creative activities to attract the hearts of these child users as a manifestation of the librarian's role in fostering a love of literacy. since early stage.